FOODPORN, FOODGASM DAN MITOS DALAM MAKANAN (ANALISIS SEMIOTIKA MEDIA PROMOSI WARUNG BABI GULING CANDRA DI DENPASAR) - Suryanatha, Ida Bagus; Zuryani, Nazrina; Nugroho, Wahyu Budi (JURNAL ILMIAH SOSIOLOGI (SOROT), 2017)
ABSTRACT Bali is famous with many traditional food, one of the famous is babi guling. Local people until foreign tourists have been know about babi guling. Many Babi Guling Warungâ€™s or some restaurant is famous here and have a some unique things every menu, but is not all of the Babi Guling Warungâ€™s used technology for promotion. Technology is become help some babi guling warungâ€™s in Bali to share and promotion with social media, one of the example is Babi Guling Candra in Denpasar. Babi Guling Candra is also used social media to share and promotion their food, for the example: they used a banner, facebook, and also instagram. This research used descriptive-eksplanative method to find there is some â€œmythâ€ or not in the social media of Babi Guling Candra, because when a some opinion in social media, it means there is some â€œmythâ€ there. In collecting the data, the authors use the technique of observation, semi-structured interviews, and also some documentation. Based on the research that has been done by using the theory of semiology by Roland Barthes that is consists to know there is some â€œmythâ€ or not, and the authors can find it someÂ conclusion if a some babi guling opinion produces by Babi Guling Candra is didnâ€™t have some â€œmythâ€ for the every picture they already have, because when tha authors ask to informant, they said they can feel the same tasted when they are already to try it, and feel same when they are just see for the media promotion of Babi Guling Candra, and they also said if the tasted is almost same with the picture. Keywords : Babi Guling, Babi Guling Candra, Opinion, Myth